The role of NMT induction on odontogenic proliferation and differentiation of dental pulp stem cells - Effendi, Muhammad Chair (Heliyon, 2021)
This study was conducted to investigate the odontogenic proliferation and differentiation of dental pulp stem cells (DPSCs) after induction by nanoparticle mineral trioxide (NMT). DPSCs were isolated from permanent teeth and placed in tubes containing Dulbecco's modified Eagle's medium, followed by immunocytochemistry analysis. The viability of DPSCs exposed to NMT was measured using MTT assay with trypan blue dye exclusion. Alkaline phosphatase (ALP) activity was evaluated using ALP colorimetric reactions by reacting NMT supernatants with fluorescent-specific ALP substrates. The concentration of osteocalcin was determined using an instant human osteocalcin enzyme-linked immunosorbent assay (ELISA) kit. A human dentin sialophosphoprotein (DSPP) ELISA kit coated with anti-human DSPP antibody was employed to measure DSPP levels. There was a significant difference between ALP activity after exposing the cells to NMT and trioxide mineral aggregate on days 3, 7, and 21. Osteocalcin activity showed a significant difference on days 3, 7, 14, and 21. There was a significant difference in DSPP levels on days 7 and 21. DPSCs exposed to NMT and to trioxide mineral aggregate showed extracellular matrix formation on day 7 and 14, respectively. Furthermore, NMT may effectively increase the proliferation and differentiation of DPSCs as well as their maturation toward odontoblasts.